Can accidental introductions of non‐native species be prevented by fish stocking audits?. Issue 3 (22nd March 2013) - Davies, Gareth D.; Gozlan, Rodolphe E.; Robert Britton, J.
ABSTRACT: Accidental introductions of non‐native species into aquatic environments often result in invasive populations that cause substantial conservation concerns. They account for 8% of all fish introductions and often occur when fish consignments are intentionally released into the wild ('stocked') but are unknowingly contaminated with a 'hitch‐hiking' species that is also released. This study tested the efficacy of a fish stocking audit procedure in preventing the introduction of a model hitch‐hiking fish ( Pseudorasbora parva ) within a batch of model native fish ( Rutilus rutilus ). It was tested in relation to different P. parva contamination levels (1, 5, 10, 20%), auditor expertise (Expert, Intermediate, Novice) and search effort. There was considerable variability in the detection thresholds among contamination levels, auditor experience and search effort; false‐negative recordings reduced as all these parameters increased. Probability of P. parva detection (POD, 0 to 1) showed that at the lowest search effort, POD was greater than 0.80 for Expert auditors only when contamination levels exceeded 10%. At the highest search effort, POD was greater than 0.80 at the 1% contamination level for Experts, but was at 3 and 8% contamination for Intermediates and Novices. Thus, while small non‐native fishes are at risk of being accidentally introduced owing to their difficulty of detection in stocking consignments, an effective audit procedure using experienced auditors and high search effort reduces this risk. Implementation should help prevent subsequent invasions, protecting native species from their adverse ecological consequences. Copyright © 2013 John Wiley & Sons, Ltd.